Estudo bibliométrico da literatura brasileira de esquistossomose - Oliveira, Margarida Pinto (1975)
Bibliometric study designed to investigate the initiation, spread and peaking point of ideas in the scientific community. The study uses as a conceptual framework the "epidemic process" theory, drawing a parallel between the spread of ideas and the spread of communicable diseases. Specifically the study will deal with literature dealing with Brazilian Schistosomiasis from 1908 to 1972.The study will project the further growth of the number of authors writing about and literature written on this field for the years 1973-1975.An attempt will be made to evaluate the causes of the marked growth of and increased author interest in, the Schistosomiasis literature in the year 1967. The study will investigate the papers/authors ratio throughout the period. Using post 1967 multipleauthor literature as a base, the study will identify those Brazilian groups that constitute the Schistosomiasis area's Research Front. The study will investigate the formation of research groups and analyse links through Bibliographic Coupling.